2020
DOI: 10.3390/polym12071605
|View full text |Cite
|
Sign up to set email alerts
|

Film Blowing of Linear and Long-Chain Branched Poly(ethylene terephthalate)

Abstract: Film blowing of Poly(ethylene terephthalate) (PET) is challenging due its inherently low melt viscosity and poor melt strength. In this study, it is shown how the rheological properties of a commercial PET can be altered by reactive extrusion using either pyromellitic dianhydride (PMDA) or a multifunctional epoxy (Joncryl® ADR 4368) as chain extender, in order to improve the processing behavior during film blowing. The modified materials were characterized by shear and elongation rheometry and relevant process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…Figure 8 (A,B) show that the torque curves of neat PETG and neat PGA gradually shifted upward with an increase in ADR content. According to previous research [ 20 , 28 , 29 , 30 ], the multifunctional epoxide groups of the chain extender could react with both the carboxyl and hydroxyl end groups of many kinds of polyester. The resultant chain extension/branching reactions are responsible for the increase in melt viscosity of polyesters during melt processing.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8 (A,B) show that the torque curves of neat PETG and neat PGA gradually shifted upward with an increase in ADR content. According to previous research [ 20 , 28 , 29 , 30 ], the multifunctional epoxide groups of the chain extender could react with both the carboxyl and hydroxyl end groups of many kinds of polyester. The resultant chain extension/branching reactions are responsible for the increase in melt viscosity of polyesters during melt processing.…”
Section: Resultsmentioning
confidence: 99%
“…This effect is related to the strongly branched molecules and to gel structures and should be beneficial for processing applications with distinct elongational components, when the uniformity of the processed items is considered. For films blown from a high viscous PET with a laboratory equipment, it has been shown that the modification with 0.4 wt% Joncryl improves the bubble stability and the uniformity of the film thickness 56 . However, a too large gel content may lead to a reduced extensibility of the polymer melt, 56 and optical properties of the films may be negatively affected.…”
Section: Discussionmentioning
confidence: 99%
“…For films blown from a high viscous PET with a laboratory equipment, it has been shown that the modification with 0.4 wt% Joncryl improves the bubble stability and the uniformity of the film thickness 56 . However, a too large gel content may lead to a reduced extensibility of the polymer melt, 56 and optical properties of the films may be negatively affected.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the polymer experiences non-isothermal elongational flow and the overall behavior of the material is determined by its rheological response, as well as by the variation of its rheological properties with temperature and by the rate of solidification (or of crystallization for semicrystalline polymers) [61]. The rheological behavior of a polymer melt subjected to non-isothermal elongational flow is typically evaluated through Rheotens (or other very similar devices) experiments, involving the application of a uniaxial extension under a constant tensile force on the molten filament [62,63]. During this kind of test, the tensile force needed for the elongation of the extruded filament is measured as a function of the draw ratio, obtaining tensile-force vs. drawdown-speed curves [64].…”
Section: Main Features Of the Elongational Flowmentioning
confidence: 99%